1990
DOI: 10.1002/app.1990.070411138
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating polymer networks of cellulose nitrate and castor oil based polyurethanes—development and characterization

Abstract: SynopsisSemi-interpenetrating polymer networks of cellulose nitrate and castor oil based polyurethanes have been prepared by using excess diisocyanate for the crosslinking process. Semi-IPNs with 30% cellulose nitrate showed some degree of miscibility. Enhanced miscibility was observed by the partial replacement of cellulose nitrate with poly (vinyl chloride-co-vinyl acetate). The ternary IPNs of poly (vinyl chloride-co-vinyl acetate), cellulose nitrate, and polyurethanes showed increased tensile strength and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…(9) with aforementioned kinetic parameters, whereas the solid lines are obtained directly from the DSC curve data by using eqs. (7) and (8). According to the results, it can be concluded that experimental data agree very well with the theoretical prediction.…”
supporting
confidence: 85%
“…(9) with aforementioned kinetic parameters, whereas the solid lines are obtained directly from the DSC curve data by using eqs. (7) and (8). According to the results, it can be concluded that experimental data agree very well with the theoretical prediction.…”
supporting
confidence: 85%
“…3,5 It is regarded that the nitrocellulose macromolecules penetrate into PU networks, and give rise to semi-IPNs in the PU/NC samples. The X-ray diffractogram of the samples PU and PU/NC showed a broad halo commencing from 13°to 32°in 2 with lower magnitude, and there is no crystalline region.…”
Section: Effect Of Molecular Weight Of Nitrocellulose On Crosslink Dementioning
confidence: 99%
“…In order to improve the shortcomings, a semi-interpenetrating polymer networks (IPNs) of nitrocellulose and castor-oil based polyurethane (PU) has been reported. 3 Recently, the water-resistant films from PU/poly(methylacrylate-co-styrene), 4 PU/nitrocellulose, 5 PU/chitosan, 6 and PU/elaeostearin 7 coatings to regenerated cellulose films were satisfactorily investigated in our laboratory. It was verified that the PU prepolymers in the coatings play an important role in forming IPNs, semi-IPNs, or grafted IPNs, and give rise to a share network crosslinked with cellulose and coating, which results in the strong interfacial bonding.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are characterized by the presence of two networks strongly entangled ideally only by topological constraints [3, 4]. Interpenetrating polymerization is a mode of blending two polymers to produce a mixture in which phase separation is not as extensive as it would be otherwise [5, 6]. IPNs synthesized so far exhibit various degrees of phase separation depending mainly on the miscibility of polymers [7–9].…”
Section: Introductionmentioning
confidence: 99%